If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -70 = 3x + -90 Reorder the terms: -70 + 5x = 3x + -90 Reorder the terms: -70 + 5x = -90 + 3x Solving -70 + 5x = -90 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -70 + 5x + -3x = -90 + 3x + -3x Combine like terms: 5x + -3x = 2x -70 + 2x = -90 + 3x + -3x Combine like terms: 3x + -3x = 0 -70 + 2x = -90 + 0 -70 + 2x = -90 Add '70' to each side of the equation. -70 + 70 + 2x = -90 + 70 Combine like terms: -70 + 70 = 0 0 + 2x = -90 + 70 2x = -90 + 70 Combine like terms: -90 + 70 = -20 2x = -20 Divide each side by '2'. x = -10 Simplifying x = -10
| 54=1/6w | | -6=d/3 | | Y=-7/3x-4 | | 1/6w=54 | | 9.3=31n | | 1+2=2+7 | | 0=2x^4-4x^2-48 | | X=7/3y-4 | | 3a+21=4a-60 | | 23n+5n-24n-4n+10n-3=17 | | I=1000-40r | | 10/8=8x/10 | | -2(x-6)/7=35 | | 2y=3x+21 | | 90=22.50c | | y=2x^4-4x^2-48 | | 1/3x-9=8 | | -52=4z | | 3k-74=2k-8 | | -9+5(6h-3)= | | f(x)=2x^4-4x^2-48 | | f(x)=(-3)(-1)-2 | | 9k+k-5k-k+5=45 | | H-2=-12 | | 3c+5=16c-99 | | 6(-7+9y)= | | 14k+25=4k+95 | | 15/16x-11/19y=-3 | | (5x^6+8y^2)(5x^6+8y^2)= | | 2x+3=4cx+5 | | 5(3x+1)=7(5x+7)+2 | | 89j+4=23j+70 |